2019
DOI: 10.1097/corr.0000000000000848
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Applications and Limitations of Artificial Intelligence for Fracture Detection and Classification in Orthopaedic Trauma Imaging? A Systematic Review

Abstract: Background Artificial-intelligence algorithms derive rules and patterns from large amounts of data to calculate the probabilities of various outcomes using new sets of similar data. In medicine, artificial intelligence (AI) has been applied primarily to image-recognition diagnostic tasks and evaluating the probabilities of particular outcomes after treatment. However, the performance and limitations of AI in the automated detection and classification of fractures has not been examined comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 31 publications
1
86
0
7
Order By: Relevance
“…Artificial intelligence, machine learning and deep learning have the potential to greatly improve musculoskeletal imaging in the near future (Langerhuizen et al., 2019). Machine learning algorithms have been applied to image interpretation and fracture recognition, and deep convolutional neural networks have been shown to perform better than clinicians in detecting fractures on radiographs (Lindsey et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence, machine learning and deep learning have the potential to greatly improve musculoskeletal imaging in the near future (Langerhuizen et al., 2019). Machine learning algorithms have been applied to image interpretation and fracture recognition, and deep convolutional neural networks have been shown to perform better than clinicians in detecting fractures on radiographs (Lindsey et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic review addressed the promise and potential utility in fracture care, and found computer vision was nearly as good as and even outperformed humans in detecting certain common fractures. 9 When classifying proximal humerus fractures, often misdiagnosed due to variable presentation, a CNN outperformed general physicians and general orthopaedic surgeons, but with the same performance as specialized upper extremity surgeons. The CNN was trained on ~2000 radiographs classified according to the Neer classification.…”
Section: Part Ii: Three Forms Of Machine Learning To Aid Clinical Decmentioning
confidence: 97%
“…The AI cannot be developed by computer scientists in isolation but requires ongoing and active input from clinicians. Involving orthopaedic consultants in development of AI ensures achieving maximum benefit for patients [42] and will take into account all necessary health and safety, ethical, governance, legal regulation, and health service management considerations One area in which AI is impacting to benefit orthopaedic practice is for fracture detection, which incorporates AI algorithms into the medical image analysis (Langerhuizen et al, 2019) [43].…”
Section: Application Of Artificial Intelligence In Orthopaedicsmentioning
confidence: 99%